Servant leadership and effective changes management in schools - Ibrahim, Izani; Don, Yahya (IJSRP.ORG, 2014)
Effective leadership is one of the important indicators to determining the change management in school achievement.This study aimed to identify the influence of servant leadership on the change management in schools. This cross-sectional survey involved 342 secondary school teachers in the northern zone (Perlis, Kedah, Penang and Perak). The instrument included Servant Leadership Scale (SLS) and Change Facilitator Style Questionnaire (CFSQ).Results showed that servant leadership contributed to the change management in schools. Implications of this study is servant leadership contributed to the change management in schools.Thus, servant leadership should be applied and practiced by school leaders to improve the success of change management, thereby improving school performance .